Pericranial flap for inner lining in nasal reconstruction - Sertel, Serkan; Pasche, Philippe (Annals of plastic surgery, 2016)
The general principle in nasal reconstruction is to reconstruct the 3 layers of skin, cartilage, and mucosa. Reconstructing the inner lining remains a challenge especially when adjacent tissues are not available after tumor resection. The galea and pericranial flaps (PFs) are widely used in anterior skull base reconstructive surgery. - We evaluated the use of the PF for the inner nasal lining in an anatomical cadaver study and present its clinical application in patients with benign and malignant tumors of the nose and anterior skull base. - Methods - Four fresh cadavers were injected with red-colored silicone for determining the pattern of vascularization of supraorbital (SOA) and supratrochlear (STA) arteries of each PF. Four surgical cases (2 nasocranial meningiomas, 1 nasal melanoma, and 1 nasal squamous cell carcinoma) received PF for reconstruction of inner lining. - Results - The median distances between the superior orbital rim and the division of the deep and superficial branches of STA and SOA were 8 ± 3.3 mm and 8 ± 3.7 mm, respectively. The maximum measured distance was 11 mm. The SOA provided the longest axial vascularization (70.7 ± 13. 9 mm) compared with STA (35 ± 10.4 mm). Median length of PF for subtotal nasal reconstruction including tip and columella were 70 ± 5 mm and 22.5 ± 3.5 mm, respectively. - Three cases were successfully reconstructed with PF up to the distal border of the upper lateral cartilage. In 1 patient, distal necrosis of tip and columella occurred. - Conclusions - The blood supply of the PF is mainly based on the SOA arteries. Thus, superficial dissection must end 15 mm above the orbital rim to ensure the survival of the flap. Pericranial flap can be applied for inner lining in combined nasocranial, septal, and nasal defects with extension down to the distal border of the upper lateral cartilage. Vascularization is reliable in flaps up to a length of 70 mm.
Gesehen am 05.05.2020